THE SACRED VALUES OF THE TAUH DANCE IN THE KENDURI SKO CEREMONY IN THE PULAU SANGKAR VILLAGE COMMUNITY: NILAI-NILAI SAKRAL TARI TAUH DALAM UPACARA KENDURI SKO PADA MASYARAKAT DESA PULAU SANGKAR - Liza Azoni; Indrayuda Indrayuda (LLDIKTI Wilayah X, 2023)
This article aims to reveal the sacred values of the Tauh dance in the Kenduri Sko ceremony for the people of Pulau Sangkar Village, Kerinci Regency. The Tauh dance as a cultural heritage of the Pulau Sangkar people has been preserved to this day, and is demonstrated in the Kenduri Sko ceremony. This research is qualitative with descriptive method. Qualitative data were collected through interviews, observation, and documentation studies. Informants who are traditional holders and local scholars and humanists were selected by snowball sampling. The research instrument is the researcher himself, assisted by various audiovisual aids. The data were analyzed based on the Miles and Huberman model, and determined cultural themes. The results of the study found that the sacred values contained in the Tauh dance are: 1) Human values with God, which are manifested in the form of praying, greetings, and worship; 2) The value of human relations with humans, which is manifested through human activities such as preparing for dance performances, interaction, and communication during performances; 3) The value of human relations with nature is manifested in the form of offerings in the form of incense and natural energy that enters the dancer's body.